2017
DOI: 10.1136/neurintsurg-2017-013318
|View full text |Cite
|
Sign up to set email alerts
|

Transvenous embolization of dural carotid cavernous fistulas: the role of liquid embolic agents in association with coils on patient outcomes

Abstract: In this study, in comparison with the use of coils alone, the association of transvenous embolization with liquid embolic agents for DCCF treatment resulted in higher rates of complete occlusion without increasing complication rates. The clinical outcome at the 6-month follow-up showed significant improvement in ocular symptoms over cranial nerve palsy regression, which was independent of the embolic agent chosen for treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 30 publications
2
37
0
Order By: Relevance
“…Although recent studies reported higher dCCF occlusion rates with liquid embolic materials than with coils alone and durable mid- and long-term results, treatment with liquid embolic agent may result in the occlusion of arterial collaterals and cause cranial nerve ischemia 3)7)8). In this case, we did not use any embolic materials to achieve complete occlusion because small feeders from the branches of the internal carotid artery may be compromised.…”
Section: Discussionmentioning
confidence: 91%
“…Although recent studies reported higher dCCF occlusion rates with liquid embolic materials than with coils alone and durable mid- and long-term results, treatment with liquid embolic agent may result in the occlusion of arterial collaterals and cause cranial nerve ischemia 3)7)8). In this case, we did not use any embolic materials to achieve complete occlusion because small feeders from the branches of the internal carotid artery may be compromised.…”
Section: Discussionmentioning
confidence: 91%
“…Embolization can be done with coils, liquid embolic agents, or a combination of the two, with cure rates around 85% and low morbidity and mortality. We chose to inject Histoacryl® instead of Onyx® inside the superior ophthalmic vein to avoid creating a mass effect, a complication related when using this last embolic agent [18].…”
Section: Discussionmentioning
confidence: 99%
“…Onyx embolization is less controlled than coil placement, however, this material is associated with a higher rate of complete obliteration [9]. Furthermore, because Onyx is less thrombogen-ic than coils, paradoxical worsening occurs less frequently after Onyx embolization.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of an Onyx plug in the CS is challenging, given the shunted flow and high pressure. Thus, in previous reports, coils were inserted before injecting Onyx to act as a template for the material [5,9,15].…”
Section: Discussionmentioning
confidence: 99%